Inventory Of Ectoparasites On Common Carp (Cyprinus carpio L.) In Ngrajek Village, Mungkid District, Magelang Regency - Fatikasari, Rindiani; Nofreeana, Andri; Mujtahidah, Tolibah (Universitas Teuku Umar, 2024)
Carp is a type of freshwater fish that has high economic value and is widely cultivated because it grows quickly and is easy to spawn. Often there are obstacles in carrying out cultivation activities, one of which is caused by ectoparasites. This research aims to determine the types of ectoparasites and to determine the level of prevalence and intensity of ectoparasites found in goldfish fry in Pokdakan Mina Abadi Sejahtera, Ngrajek Village, Mungkid District, Magelang Regency. The research was conducted from December 2022- January 2023. Fish samples were taken for 3 weeks with a total of 20 fish/pond in 1 week. Every time a sample was taken, abiotic factors were measured, namely temperature, pH, DO and ammonia. Ectoparasite examination was carried out at the Tidar University Laboratory and LPKIL Muntilan using the mucus scraping method on the surface of the body and biopsy, namely taking a small portion of the fin and gill organ tissue. The results of the research found ectoparasites from the Protozoa phylum, namely Trichodina sp. and Ichthyopthyrius multifiliis, the Vermes phylum, namely Dactylogyrus sp., and the Arthropoda phylum, namely Argulus sp. The highest prevalence value was obtained by Trichodina sp. in pool 2 it was 100% with the always infection category. The highest intensity value was Trichodina sp. in pond 1 there were 38/head in the moderate infection category. The average water quality in pond 1 for goldfish fry is 28.29 ºC, pH 7.25, dissolved oxygen 6.88 mg/L and ammonia 0.24 mg/L. The average water quality in the pool of 2 goldfish fry was 29.92 ºC, pH 7.38, dissolved oxygen 6.88 mg/L and ammonia 0.24 mg/L. Keywords: Feed, Feed Efficiency, Lysine, Bileh Fish.